2018
DOI: 10.3126/jnhrc.v16i1.19366
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Post-Traumatic Stress Disorder after Earthquake

Abstract: Background: Prevalence of anxiety, depression and post traumatic stress disorder is high after earthquake. The aim of the study is to study the prevalence and comorbidity of commonly occurring psychological symptoms in people exposed to Nepal mega earthquake in 2015 after a year of the event.Methods: A community based, cross sectional, descriptive study was carried out in Bhumlichaur area of Gorkha district, Nepal after around 14 months of the first major earthquake. We used self-reporting questionnaire 20, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Reported anxiety scores nearly doubled in response to the pandemic, and 20% of the sample reported that symptoms were severe enough to interfere with daily routines. Increased anxiety has been observed after other extreme natural disasters (12,13), highlighting the equivalent impact of the pandemic on mental health. The close relationships between anxiety, energy intake, and food preference are a concern for future weight gain, particularly in individuals with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Reported anxiety scores nearly doubled in response to the pandemic, and 20% of the sample reported that symptoms were severe enough to interfere with daily routines. Increased anxiety has been observed after other extreme natural disasters (12,13), highlighting the equivalent impact of the pandemic on mental health. The close relationships between anxiety, energy intake, and food preference are a concern for future weight gain, particularly in individuals with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the global context, very wide prevalence ranges have been identified for both PTSD (0% to 99%) and depression (3% -85.5%) in trauma-exposed populations [26]. The latest community level studies on earthquake affected victims of Nepal have reported the rates of PTSD as 27% in the 14 th month after the earthquake [27] and 24% in the 20 th month after the earthquake [28]. Despite the high prevalence of PTSD, diagnosing trauma related disorders in clinical practice is not common in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…The rates with which certain disorders presented at the clinics in this program differed from global prevalence estimates, which suggest that depression, followed by anxiety, and AUDs would be the most prevalent disorders (James et al ., 2018; Thapa et al ., 2018). Epilepsy was the most common presenting problem, followed by depression, and psychosis.…”
Section: Discussionmentioning
confidence: 99%